2022
DOI: 10.3389/fnut.2021.792203
|View full text |Cite
|
Sign up to set email alerts
|

Pulsed Electric Field-Assisted Extraction of Aroma and Bioactive Compounds From Aromatic Plants and Food By-Products

Abstract: In this work, the effect of pulsed electric field (PEF) pre-treatment on the extractability in green solvents (i. e., ethanol–water mixture and propylene glycol) of target aroma and bioactive compounds, such as vanillin from vanilla pods, theobromine and caffeine from cocoa bean shells, linalool from vermouth mixture, and limonene from orange peels, was investigated. The effectiveness of PEF as a cell disintegration technique in a wide range of field strength (1–5 kV/cm) and energy input (1–40 kJ/kg) was confi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(21 citation statements)
references
References 42 publications
0
17
0
Order By: Relevance
“…PEF treatments of artichoke stems were performed using a laboratory-scale batch system previously described [ 30 ]. Briefly, the apparatus consisted of a high-voltage pulsed power (25 kV–500 A) generator (Modulator PG, Scandi Nova, Uppsala, Sweden) capable of delivering monopolar square wave pulses (3–25 µs, 1–450 Hz) to the plant matrix placed between two plane parallel electrodes of stainless steel separated by a Teflon spacer (4 cm electrode gap, 75 cm 2 electrode area).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…PEF treatments of artichoke stems were performed using a laboratory-scale batch system previously described [ 30 ]. Briefly, the apparatus consisted of a high-voltage pulsed power (25 kV–500 A) generator (Modulator PG, Scandi Nova, Uppsala, Sweden) capable of delivering monopolar square wave pulses (3–25 µs, 1–450 Hz) to the plant matrix placed between two plane parallel electrodes of stainless steel separated by a Teflon spacer (4 cm electrode gap, 75 cm 2 electrode area).…”
Section: Methodsmentioning
confidence: 99%
“…The high-performance liquid chromatography–photodiode array detection (HPLC–PDA) analysis for the identification of phenolic compounds in the extracts from both untreated and PEF-treated artichoke stems was performed using a Waters 1525 Separation Module coupled to a photodiode array detector, Waters 2996 (Waters Corporation, Milford, MA, USA), following a modified method reported by Carpentieri et al [ 30 ]. Analytical separation of the identified compounds was carried out in a Waters Spherisorb C18 reverse-phase column (5 μm ODS2, 4.6 × 250 mm, Waters Corporation, Milford, MA, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The drawback of this technology is the damage produced in the cell membrane when the following conditions are applied—between 500 and 1000 V/cm, for 10-4-10-2 s—due to a minor expansion in the temperature. However, PEF is a highly selective method with low energy cost, low time of extraction, and low quantity of solvent requirement [ 15 ]. Moreover, a study has shown that, in this technology, the plant cells are destroyed, allowing an increase in the extraction yield of bioactive compounds from plant tissues.…”
Section: Extraction Techniquesmentioning
confidence: 99%
“…There are no data on nut aromas, although the positive effect of this treatment on the extraction of aroma in plants or the preservation of these aromas in food processing, fruits juices and vegetables has been demonstrated. These changes could be possible due to the fact that PEF induces cell permeabilization, facilitating enzyme-substrate reactions after the treatment [ 49 , 50 , 51 , 52 , 53 , 54 ].…”
Section: Non-thermal Treatmentsmentioning
confidence: 99%